Helicobacter pylori infection as an independent risk factor for cerebral ischemia of atherothrombotic origin - Grau, Armin J.; Buggle, Florian; Lichy, Christoph; Brandt, Tobias; Becher, Heiko; Rudi, Jochen (Journal of the neurological sciences, 2001)
Chronic infection may increase the risk for ischemic stroke. Presently, it is insufficiently established whether Helicobacter pylori infection represents a risk factor for ischemic stroke. We analyzed IgG antibodies against H. pylori in 109 patients with acute cerebral ischemia and 82 age- and sex-matched control patients with non-vascular and non-inflammatory neurological diseases. Antibody titers were significantly higher in patients than in control subjects (p=0.007). H. pylori seropositivity tended to be more common in patients (odds ratio (OR) 1.55, 95% confidence interval (ci) 0.87-2.76), but this trend was further attenuated in multivariate analysis (OR 1.42; 95% 0.75-2.67) with hypertension, diabetes mellitus, current or previous smoking, previous cerebral ischemia and low socioeconomic status. H. pylori seropositivity increased the odds for cerebral ischemia of atherothrombotic origin in univariate (OR 3.63; 95% ci 1.37-9.65) and multivariate analysis (OR 3.53; 95% ci 1.09-11.4). H. pylori seropositivity may be an independent risk factor for stroke of atherothrombotic origin.
Gesehen am 14.10.2021